Question
upstudy study bank question image url

Find the derivative of the function \( B(t)=\sqrt[3]{\frac{t}{3 t^{2}+4}} \)

Ask by Vaughan Bartlett. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( B(t) = \sqrt[3]{\frac{t}{3t^2 + 4}} \) is: \[ B′(t) = \frac{4 - 3t^2}{3 \cdot t^{2/3} \cdot (3t^2 + 4)^{4/3}} \]

Solution

We are given the function   B(t) = ∛(t/(3t² + 4)) = [t/(3t² + 4)]^(1/3). To find its derivative B′(t), we will use the chain rule along with the quotient rule. Follow these steps: Step 1. Write B(t) as a power function:   B(t) = [u(t)]^(1/3),  where u(t) = t/(3t² + 4). By the chain rule,   B′(t) = (1/3) [u(t)]^(1/3 − 1) · u′(t) = (1/3) [u(t)]^(–2/3) · u′(t). Step 2. Compute u′(t) using the quotient rule. Recall that if u(t) = f(t)/g(t), then   u′(t) = [g(t) f′(t) − f(t) g′(t)] / [g(t)]². Here, f(t) = t and g(t) = 3t² + 4, so   f′(t) = 1  and  g′(t) = 6t. Thus,   u′(t) = [(3t² + 4)(1) − t(6t)] / (3t² + 4)²        = [3t² + 4 − 6t²] / (3t² + 4)²        = (4 − 3t²) / (3t² + 4)². Step 3. Substitute u(t) and u′(t) back into the expression for B′(t):   B′(t) = (1/3) [t/(3t² + 4)]^(–2/3) · [(4 − 3t²)/(3t² + 4)²]. To simplify the expression [t/(3t² + 4)]^(–2/3), note that a negative exponent inverts the fraction:   [t/(3t² + 4)]^(–2/3) = (3t² + 4)^(2/3)/t^(2/3). Now substitute this back:   B′(t) = (1/3) · [(3t² + 4)^(2/3)/t^(2/3)] · [(4 − 3t²)/(3t² + 4)²]. Combine the factors involving (3t² + 4):   (3t² + 4)^(2/3) / (3t² + 4)² = 1/(3t² + 4)^(2 − 2/3) = 1/(3t² + 4)^(4/3). Thus, the derivative simplifies to:   B′(t) = (1/3) · (4 − 3t²) / [t^(2/3) (3t² + 4)^(4/3)]. So the final answer is:   B′(t) = (4 − 3t²) / [3 · t^(2/3) · (3t² + 4)^(4/3)].

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the derivative of the function \( B(t)=\sqrt[3]{\frac{t}{3t^{2}+4}} \), we can apply the chain rule and the quotient rule. Let \( u = \frac{t}{3t^{2}+4} \). Then, we can rewrite the function as \( B(t) = u^{1/3} \). 1. Differentiate \( B(t) \) using the chain rule: \[ B'(t) = \frac{1}{3} u^{-2/3} \cdot u' \] 2. Next, we find \( u' \) using the quotient rule: \[ u' = \frac{(3t^2+4)(1) - t(6t)}{(3t^2+4)^2} \] Simplifying this gives: \[ u' = \frac{3t^2+4 - 6t^2}{(3t^2+4)^2} = \frac{-3t^2 + 4}{(3t^2+4)^2} \] 3. Now substitute \( u' \) back into the derivative of \( B(t) \): \[ B'(t) = \frac{1}{3} \left( \frac{t}{3t^2+4} \right)^{-2/3} \cdot \frac{-3t^2 + 4}{(3t^2+4)^2} \] 4. Finally, putting it all together: \[ B'(t) = \frac{-1}{3} \cdot \frac{-3t^2 + 4}{3} \cdot \frac{(3t^2 + 4)^{-2/3}}{(3t^2 + 4)^2} \] This simplifies to: \[ B'(t) = \frac{(-3t^2 + 4)}{3(3t^2 + 4)^{5/3}} \] So, the derivative is: \[ B'(t) = \frac{4 - 3t^2}{3(3t^2 + 4)^{5/3}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy